Developing a Framework for Ethical Leadership (2015)
Interest in ethical leadership from academics and practitioners has grown enormously in recent years. This article addresses this literature through a framework that identifies three interlocking questions. First, who are ethical leaders and what are their characteristics? Second, how do ethical leaders do what they do? Third, why do leaders do as they do and what are the outcomes of ethical leadership? Different dimensions to ethical leadership are examined and presented as three interlocking circles; Virtues, Purposes and Practices. This framework presents an integrated approach to ethical leadership and argues that future research take this holistic framework and apply it to different sectors or contexts.